Cultural Intelligence in Hospitality Management: Leveraging Business Strategies to Enhance Guest Satisfaction in a Globalized Market - Sharma, Aaditya Shankar; Devkota, Jiwan; Pandit, Shishir; Shrestha, Jhamka Narayan; Lamichhane, Basu Dev (NPRC Journal of Multidisciplinary Research, 2025)
Background: In today's globalized hospitality industry, cultural differences significantly influence guest satisfaction, yet many hotels struggle to effectively address diverse cultural needs. While previous research has established the importance of cultural factors in service delivery, there remains limited empirical evidence on how specific cultural elements impact guest experiences in hotel settings.Objective: This study examines how cultural differences affect guest satisfaction in hotels, focusing on communication, amenities, food services, and overall cultural inclusivity. It aims to identify key areas where cultural sensitivity enhances guest experiences and provides actionable recommendations for hotel management.Methods: A quantitative research approach was employed, utilizing a structured survey of 132 hotel guests. Data was analyzed using descriptive statistics to assess perceptions of cultural inclusivity across various service dimensions, including staff communication, language barriers, dietary accommodations, and facility offerings.Findings: Results indicate that while 50.8% of guests felt cultural differences influenced their stay, 37.1% remained neutral, highlighting inconsistent cultural adaptation. Effective communication was positively rated by 40.9% of respondents, but 37.9% were neutral, suggesting room for improvement. Food options aligned with cultural preferences for 48.5% of guests, while 31.1% expressed indifference. Notably, 75% of participants agreed that hotels should enhance their cultural understanding.Conclusion: The study underscores the importance of cultural sensitivity in hotel operations, revealing gaps in current service delivery. Hotels must prioritize staff training, culturally diverse amenities, and improved feedback mechanisms to better serve international guests and boost satisfaction.Novelty: This research contributes new empirical data on specific cultural factors affecting guest satisfaction, moving beyond theoretical frameworks to provide practical, data-driven insights for hotel management. It also introduces measurable indicators for assessing cultural inclusivity in hospitality services.